Implementasi Lelang Jaminan Tanah Dengan Hak Tanggungan - amaa, Rahmatul Khasanah; Prabu, Dedy Suryandana; Indra, Indra Muclis Adnan; Syaputra, Didi (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2024)
The intent of this article is to explain how to conduct a mortgage charging auction. Normative juridical research—research conducted by looking at the subject of books or secondary information—is the method used. This method makes it possible to regard mortgage rights as a type of collateral. However, it is not clear whether the collateral stems from an agreement. Basically, mortgage laws state that mortgage grants must meet the conditions of a legal agreement. In contract law, sanctions against actual guarantees can be exercised in three ways: public auction via public execution, public auction via judicial apartments, and private sale.